Evaluation of nutrition education intervention programme on nutritional status among children below five years of age in Shabelle (Gode) Zone of Somali Region, Eastern Ethiopia - Guled, Rashid Abdi (Kulliyyah of Allied Health Science, International Islamic University Malaysia, 2018)
Malnutrition is one of the most distressing public health problems all over the world. Undernutrition is common in third world countries. It is an insufficiency of nutrients, minerals, and vitamins, that person requires to keep up the best possible strength of cells, tissues and organs. In the previous two and half decades (1990 – 2015), a great effort toward accomplishing millennium development goal (MDG) four were performed. The number of under-five mortality significantly decreased by half during this period. However, a significant number of children less than five years are still suffering and dying because of undernutrition in developing world. This lead to a negatively influences on physical wellbeing and linear growth of infants and pre-school children. Ethiopia is one of the poorest among the developing nations and undernutrition is the highest within the sub-Saharan Africa. Hence, this study aims to evaluate the effect of nutrition education intervention (NEI) on knowledge, attitude and practice (KAP) of the mothers/caregivers on infant and young child feeding (IYCF) behaviours and nutritional status of the children below five years. This study was conducted in two phases, first phase was a cross sectional study assessing mothers/caregivers KAP on IYCF and nutritional status of the children, in order to identify the gaps, plan properly, and conduct NEI. In the second phase a group randomized controlled trial design were employed. When selecting the intervention and control districts the socio-demographic, economic and life style similarities were taken into consideration. A total of 415 in phase one and 404 in phase two child-mothers/caregivers pairs participated in the study from Gode and Adadle districts of Shabelle zone. Semi structured interviewer administered questionnaire, anthropometric, blood sample assessment were performed. At baseline study using multivariable logistic regression showed being in Gode District (p <0.001), and not being housewife (p <0.05) were significantly associated with having good knowledge about optimal infant and young child feeding (IYCF), and wealth index (p <0.01) were positively associated with favourable attitude, and being literate (p <0.01) is positively associated with good practice. At post intervention, the KAP of mothers/caregivers mean score improved significantly after NEI. Paired sample t-test showed that KAP mean score of mothers/caregivers significantly (p <0.001) improved after intervention. Similarly, independent t-test mean score difference of the difference (DOD) were significantly improved (p <0.001) in all three variables compared to control group. Likewise, the mean Z-score of wasting (p <0.001) and underweight (p <0.01) of the children within the group were significantly improved in intervention group. This was not seen in stunting, which was almost similar in both phases. Nonetheless, control group showed a significant worsening mean Z-score for wasting, underweight, and stunting (p <0.05) that indicates the worsening of the children nutritional status. Regarding the anaemia status of the children, the mean score showed statistically significant improvement (p <0.001), after NEI in both groups. But, the intervention group has significantly higher increment. In conclusion, NEI had shown improvement of maternal/caregivers KAP related to IYCF behaviours. Thus, subsequently improved the nutritional status of the children. Therefore, NEI should be scaled up and expanded to rural communities in sustainable manner, an especial attention should be given to those families and communities with poor wealth index and food insecure by provision of accessible, available and affordable food items and services at grass root level.